Language Use : An Analysis Of Expressive Acts Used by The Eleventh Grade Students of SMA Negeri 2 Singaraja - ., Ida Ayu Teguh Kesari Wirata; ., Prof. Dr. Dewa Komang Tantra,Dip.,App.; ., Dewa Putu Ramendra, S.Pd, M.Pd (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
This study was a qualitative research. This study intended : 1) to identify and classify the types and the pettern of expressive used by the eleventh grade students at SMA N 2 Singaraja in expressive. 2) to identify the style of the students locutionary acts to express something. 3) to identify and classify the types of errors are committed by eleventh grade students at SMA N 2 Singaraja expressing their idea in terms of grammar and diction 4) to analyze the source of error as committed by the students’ locutionary acts.The subject of this study were eleventh grade students of SMAN 2 Singaraja. The data were collected by using several instrument, namely: note, interview guide and recorder. The results of the study showed that 1) The types of expressive acts were used among the eleventh grade students at SMA N 2 Singaraja were apologizing, thanking, congratulating, and welcoming. 2) The speech style used in terms of formality among the eleventh grade students at SMA N 2 Singaraja were 78.01% informal language and 21.99% formal language. 3) The errors are commited in their utterances in terms of grammar and diction at SMA N 2 Singaraja were 54.03% error of grammar and 45.97% error of diction. 4) The source of errors were commited by the eleventh grade students at SMA N 2 Singaraja were called as interlanguage errors. These errors happed when the interference of students’ first language occured in the target language. In other words, the students assumed that the structures of their first language are the same with the target language. Kata Kunci : Key Words: expressive acts, formal style, informal style, errors, source of errors This study was a qualitative research. This study intended : 1) to identify and classify the types and the pettern of expressive used by the eleventh grade students at SMA N 2 Singaraja in expressive. 2) to identify the style of the students locutionary acts to express something. 3) to identify and classify the types of errors are committed by eleventh grade students at SMA N 2 Singaraja expressing their idea in terms of grammar and diction 4) to analyze the source of error as committed by the students’ locutionary acts.The subject of this study were eleventh grade students of SMAN 2 Singaraja. The data were collected by using several instrument, namely: note, interview guide and recorder. The results of the study showed that 1) The types of expressive acts were used among the eleventh grade students at SMA N 2 Singaraja were apologizing, thanking, congratulating, and welcoming. 2) The speech style used in terms of formality among the eleventh grade students at SMA N 2 Singaraja were 78.01% informal language and 21.99% formal language. 3) The errors are commited in their utterances in terms of grammar and diction at SMA N 2 Singaraja were 54.03% error of grammar and 45.97% error of diction. 4) The source of errors were commited by the eleventh grade students at SMA N 2 Singaraja were called as interlanguage errors. These errors happed when the interference of students’ first language occured in the target language. In other words, the students assumed that the structures of their first language are the same with the target language. keyword : Key Words: expressive acts, formal style, informal style, errors, source of errors